The Operating Improvement of the Supply Source and the Optimization of PWM Control - Farouk Hadj Benali; Fouad Azzouz; Ghalem Bachir (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In this paper the operating improvement of the supply source and the optimization of PWM control are proposed. A comparison (based on the better operating in terms of input voltage) between the multilevel inverters (NPC multilevel inverter and H bridge inverter) is studied. Then two control strategies (the SPWM and the suboptimal PWM) are applied to the multilevel inverter which has the better voltage performance. At last a comparison between these two control techniques based on two essential points, the THD and the output voltage value. A comparison between our results and results taken from literature is also presented in this paper. Simulations are carried out using PSIM environment.